Symposium 13: Towards an Ecology of Networked Learning: Symposium Introduction - Ponti, Marisa (Proceedings of the International Conference on Networked Learning, 2004)
This Symposium is part of the work of a Special Interest Group (SIG) in the EU funded project “EQUEL” – e[1]quality in e-learning. The SIG is interested in the application of technology and development of theory as developed within the research community on networked learning environments. This research community commonly acknowledges that human interaction and communication as well as technological tools are key factors to developing an ecology of collaboration, in which social and communicative processes and mediating technology integrate into a uniquely situated learning context. Following Nardi and O’Day (1999), ecology is the evolving environment that supports collaborative learning, integrates artefacts, technologies, and spaces for acting, and allows for diverse individual roles and technical functions.